ANALISIS YURIDIS CABANG PEMERINTAHAN KEEMPAT DALAM STRUKTUR KETATANEGARAAN DI INDONESIA - Tri Suhendra Arbani (Universitas Slamet Riyadi, 2018)
The development of the modern state system is also followed by the establishment of new institutions as a support of the institutions that have been there before. The most significant event in the development and establishment of institutions is the new power branch, which is called by the experts in constitutional as an independent state commission. Independent state commission institution which, if seen from the character and the authority, the agency in some literature in American constitutional law is referred to as the fourth branch of power (The Fourth Branch of Government). Some things that make this institution called the fourth branch of government (The Fourth Branch of Government) is the fact that the agency, or commission or the state body run more than one function of government as well. The existence of a fourth branch of government (The Fourth Branch of Government) with the characteristics of state institutions whose authorities are quasi, combinations, as well as the accumulation of three existing government functions and make this institution to be difficult to identify in thought Trias Politica. The phenomenon of the rise of an institution with a new concept that has influenced the constitutional system in many countries.